Strategy for Implementing the Merdeka Curriculum at SMP in Labuhan Haji Barat - victorini, yulia; Rahmattullah, Rahmattullah; Khausar, Khausar (Journal of English Language and Education, 2025)
This research aims to identify and analyze the implementation strategies of the Merdeka Curriculum in order to improve the quality of education at the Junior High School (SMP) level in the Labuhan Haji Barat District. This research uses a qualitative approach with a case study method. Data were obtained through in-depth interviews, direct observations, and document analysis involving school principals, teachers, supervisors, and school committees as key informants. The research results show that schools in the Labuhan Haji Barat District have implemented several important strategies, including: strengthening the role of school principals as learning leaders, forming teacher practitioner communities, utilizing the Merdeka Mengajar digital platform, and implementing projects based on local wisdom. The main challenges faced include the low digital literacy of some teachers, limited infrastructure, and relatively high administrative demands. These findings indicate that to optimize the implementation of the Merdeka Curriculum, it is crucial to maximize the leadership of school principals and the existing culture of teacher collaboration to leverage online training and digital learning resources. Integrate the Pancasila Student Profile project with local themes to increase student interest. This study recommends strengthening teachers' digital literacy, improving infrastructure, and encouraging sustainable collaboration to enhance the impact of curriculum implementation.